Thermal conductivity of aligned CNT/polymer composites using mesoscopic simulation. (November 2016) - Zhou, Bing; Luo, Wan; Yang, Jiaqiang; Duan, Xianbao; Wen, Yanwei; Zhou, Huamin; Chen, Rong; Shan, Bin
Abstract: Thermal conductivity of CNT/polymer composites depends on alignment, dispersion, volume fraction and size of CNTs as well as polymer size. By coupling smoothed particle hydrodynamics and dissipative particle dynamics, thermal conductivities of random and aligned composites along with their meso morphologies are studied in detail. Thermal conductivity along the alignment of CNT can be significantly enhanced to 16 times that of polymer by increasing volume fraction, dispersion degree and length of CNT, meanwhile thermal conductivity perpendicular to the alignment of CNT is affected modestly by these factors. Enhancement of thermal conductivity of random composites could only be efficiently achieved by increasing the volume fraction of CNT. Particularly, thermal conductivity κ is proportional to the square of volume fraction of CNT v in well dispersed random and aligned composites, i.e. κ ∝ v 2 .